Helicopter Handling Qualities: A study in pilot control compensation. (16th January 2022) - Memon, W.A.; White, M.D.; Padfield, G.D.; Cameron, N.; Lu, L.
Abstract: The research reported in this paper is aimed at the development of a metric to quantify and predict the extent of pilot control compensation required to fly a wide range of mission task elements. To do this, the utility of a range of time- and frequency-domain measures to examine pilot control activity whilst flying hover/low-speed and forward flight tasks are explored. The tasks were performed by two test pilots using both the National Research Council (Canada)'s Bell 412 Advanced Systems Research Aircraft and the University of Liverpool's HELIFLIGHT-R simulator. Handling qualities ratings were awarded for each of the tasks and compared with a newly developed weighted adaptive control compensation metric based on discrete pilot inputs, showing good correlation. Moreover, in combination with a time-varying frequency-domain exposure, the proposed metric is shown to be useful for understanding the relationship between the pilot's subjective assessment, measured control activity and task performance. By collating the results from the subjective and objective metrics for a range of different mission task elements, compensation boundaries are proposed to predict and verify the subjective assessments from the Cooper-Harper Handling Qualities Rating scale.